From Silica Nanoparticles (SiNPs) to Bio-Quantum Interfaces: Innovations in Water Purification, Photoprotection, and Emerging Energy Sensing Technologies - Yehia, Hesham Mohamed Abd Al-Salam (European Journal of Applied Sciences, 2025)
Expanding upon the principles of utilizing natural materials, emerging research into Quantum Plasma Energy Technology (QPET) presents a revolutionary frontier for non-invasive health and environmental monitoring. Inspired by the theoretical concept that the human biofield, including the energy emissions from the plasma s, can interact with quantum-scale phenomena, QPET seeks to develop ultra-sensitive detectors. These detectors, potentially leveraging nanostructured materials like the mesoporous silica discussed in this study, could be engineered to resonate with specific biological or environmental energy signatures. For instance, a QPET sensor could be conceptualized to assess the "vitality" or pH-altering efficacy of water treated with our silica-based substance by measuring subtle, coherent energy exchanges, offering a holistic assessment beyond conventional chemical metrics. This research demonstrates the significant potential of engineered natural silica as a multifunctional material for promoting health and sustainability. By providing a safe alternative to chemical water alkalizers, it addresses public health concerns in water purification. Simultaneously, the development of Octa-H presents an innovative approach to photoprotection, transforming harmful solar radiation into a beneficial form while also leveraging silica’s advantageous properties in cosmetic science. Together, these applications underscore a promising pathway toward achieving sustainable development goals through material science innovation, emphasizing safety, natural origins, and enhanced human well-being.